AN OFDM platform for wireless systems testing: alamouti 2x1 MIMO example - Violas, Manuel (2015)
In this paper, we present a real-time implementation of an OFDM hardware platform. The platform is based on HW blocks that can be put together to configure a wireless system based on OFDM modulation. The platform can be easily upgraded to test pre-coding cooperation algorithms. We evaluate the platform to implement a diversity Alamouti 2×1 MIMO scheme wireless system. The testbed is implemented using Field- Programmable Gate Array (FPGAs) through Xilinx System Generator for DSP. Blocks for time-domain synchronization and channel estimation are key components necessary in transmission system that require good time synchronization and channel estimation for efficient demodulation.